Influencing factors of interprofessional collaboration in multifactorial fall prevention interventions: a qualitative systematic review - J. S. C. Muusse; R. Zuidema; M. C. van Scherpenseel; S. J. te Velde (BMC Primary Care, 2023)
Abstract Background With the ageing population worldwide, falls are becoming a severe and growing health problem. Interprofessional multifactorial fall prevention interventions (FPIs) have effectively prevented falls in community-dwelling older adults. However, the implementation of FPIs often fails due to a lack of interprofessional collaboration. Therefore, gaining insight into the influencing factors of interprofessional collaboration in multifactorial FPI’s for older adults living in the community is essential. Consequently, our aim was to provide an overview of factors influencing interprofessional collaboration in multifactorial FPIs for community-dwelling older adults. Methods This qualitative systematic literature research was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Pubmed, CINAHL, and Embase electronic databases have been systematically searched for eligible articles, with a qualitative design. The quality was appraised using the Checklist for Qualitative Research by the Joann Briggs Institute. The findings were inductively synthesized using a meta-aggregative approach. Confidence in the synthesized findings was established using the ConQual methodology. Results Five articles were included. Analysis of the included studies resulted in 31 influencing factors for interprofessional collaboration, which were labelled as findings. These findings were summarized in ten categories and combined into five synthesized findings. Results showed that communication, role clarity, information sharing, organization, and interprofessional aim influence interprofessional collaboration in multifactorial FPIs. Conclusions This review provides a comprehensive summary of findings on interprofessional collaboration, specifically in the context of multifactorial FPIs. Knowledge in this area is considerably relevant given the multifactorial nature of falls, which demands an integrated, multidomain approach, including both health and social care. The results can be utilized as a fundament for developing effective implementation strategies aiming to improve interprofessional collaboration between health and social care professionals working in multifactorial FPIs in the community.